DESIGN OF WEB INFORMATION SYSTEM UNIVERSITAS NASIONAL: DESIGN OF WEB INFORMATION SYSTEM UNIVERSITAS NASIONAL - Nurjaman, Shandy; Wahyuddin, Moh. Iwan; Iskandar, Agus (Jurnal Mantik, 2020)
The purpose of this research is to design a system that makes it easier for the Academy's campus web college national university to easily find out academic information designed using the PHP programming language and use the Cascading Style Sheets Framework as a responsive design on the national university academic campus in helping students and users others can get campus information, lecturer information, and student data. The results showed that the Academic Information System makes it easy to manage data on the web-based academic information system on the national university's Academy Campus. With features in managing academic data that is checking student data and simplifying and improving campus performance in informing students about campus information. Furthermore, a web-based academic information system will be implemented at the Academic Campus of the national university arranged as a guide for students taking courses. By structuring it so that students will know the various technologies that underlie the web today. Web technology that is practiced in the guidelines on the web lecture is very dependent on the students' efforts to develop it further. On the other hand, this guideline was prepared in the hope that students could easily participate in the activities